Women criminals and their life-style - Maniyar, Mridula (New Delhi : Kaveri Books, 2004)
With reference to India.
Includes statistical tables.
Includes bibliographical references (p. [31]-331) and index.
Keywords: Female offenders -- India; Female offenders -- India -- Social conditions